FinTech Study Latvia 2020 - Rupeika-Apoga, Ramona; Romānova, Inna; Grima, Simon; University of Latvia. Faculty of Business, Management and Economics (University of Latvia, 2020)
This study provides an overview of the current state and the developments in the Latvian FinTech environment. This is also the first attempt of the research team at the Faculty of Business, Management and Economics of the University of Latvia to explore the Latvian FinTech landscape and increase the visibility of Latvian FinTechs and is part of a larger European survey targeting FinTechs in Eastern Europe.
Keywords: FinTech, Latvia; Research Subject Categories::SOCIAL SCIENCES::Business and economics